2002
DOI: 10.1159/000066680
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cutaneous Bioavailability of Cosmetic Preparations Containing Caffeine or α-Tocopherol Applied on Human Skin Models or Human Skin ex vivo at Finite Doses

Abstract: The use of human skin models for performing cutaneous bioavailability studies has been little investigated. For instance, only few studies have been reported on human skin models dealing with vehicle effects on percutaneous penetration. The present study aimed at evaluating the influence on caffeine’s and α-tocopherol’s cutaneous bioavailability of cosmetic vehicles such as a water-in-oil emulsion, an oil-in-water emulsion, a liposome dispersion and a hydrogel applied at finite dose using the reconstructed hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The need for a suitable model for permeability testing has necessitated the development and evaluation of several tissue-cultured in vitro skin models, frequently known as bioengineered skin substitutes or skin equivalents (SEs). Skin equivalents have been developed and researched over the past years for various applications, mainly as skin replacements in burns or wounds (3,4), for skin biology research (5), for cutaneous irritation and toxicity testing (6,7) and as models for permeability testing of agents and formulations (8,9). These skin substitutes are cultured in a controlled environment, thus increasing reproducibility and reducing scope for larger standard deviations normally encountered with human skin data.…”
Section: Introductionmentioning
confidence: 99%
“…The need for a suitable model for permeability testing has necessitated the development and evaluation of several tissue-cultured in vitro skin models, frequently known as bioengineered skin substitutes or skin equivalents (SEs). Skin equivalents have been developed and researched over the past years for various applications, mainly as skin replacements in burns or wounds (3,4), for skin biology research (5), for cutaneous irritation and toxicity testing (6,7) and as models for permeability testing of agents and formulations (8,9). These skin substitutes are cultured in a controlled environment, thus increasing reproducibility and reducing scope for larger standard deviations normally encountered with human skin data.…”
Section: Introductionmentioning
confidence: 99%
“…In permeation studies, it was found that the maximum transport rate was reached faster in the EpiDerm model when compared to native human skin; however, a prolonged application of hydrogel on the skin model leads to a decrease in permeation. Overall, the rank order of permeability was about the same between the model and the human skin . Another transport study, this time with the lipophilic drug flufenamic acid, demonstrated a higher permeation and transport rate in the model than in the native tissue…”
Section: In Vitro Epidermal Skin Equivalentsmentioning
confidence: 72%
“…Another study found that the concentration of surfactants needed to trigger a reaction in the model was lower than that was needed in vivo . In permeability studies, caffeine permeation was monitored and found to exhibit the same behavior as the human skin …”
Section: In Vitro Epidermal Skin Equivalentsmentioning
confidence: 99%
“…Correlations between in vitro and in vivo experiments have been shown previously (1–4). Thus, for example, for bioequivalence studies, in vitro experiments are beneficial to determine the difference between two vehicles (5).…”
Section: Introductionmentioning
confidence: 99%